Cyprinus carpio Skeleton Byproduct as a Source of Collagen for Gelatin Preparation - Gál, Robert; Mokrejš, Pavel; Pavlačková, Jana; Janáčová, Dagmar (International journal of molecular sciences, 2022)
Byproducts obtained from fish processing account for up to 70% of their live weight and represent a large amount of unused raw materials rich in proteins, fats, minerals, and vitamins. Recently, the management of the use of predominantly cold-water fish byproducts has become a priority for many processing companies. This paper describes the biotechnological processing of byproducts of warm-water Cyprinus carpio skeletons into gelatins. A Taguchi experimental design with two process factors (HCl concentration during demineralization of the starting material and the amount of enzyme during enzyme conditioning of the collagen) examined at three levels (0.5, 1.0 and 2.0 wt%; 0.0, 0.1 and 0.2 wt% respectively) was used to optimize the processing of fish tissue into gelatin. Depending on the preparation conditions, four gelatin fractions were prepared by multi-stage extraction from the starting material with a total yield of 18.7-55.7%. Extensive characterization of the gel-forming and surface properties of the prepared gelatins was performed. Gelatins belong to the group of zero-low-medium Bloom value (0-170 Bloom) and low-medium viscosity (1.1-4.9 mPa·s) gelatins and are suitable for some food, pharmaceutical, and cosmetic applications. During processing, the pigment can be isolated; the remaining solid product can then be used in agriculture, and H3PO4Ca can be precipitated from the liquid byproduct after demineralization. The carp byproduct processing technology is environmentally friendly and meets the requirements of zero-waste technology.
Keywords: Animals; Gelatin; circular economy; Collagen; kapři; collagen; kolagen; biopolymers; biotechnology; skeletons; by-product; gelatin; sustainable polymers; voda; Water; Skeleton; Cyprinus carpio; kostra; želatina; Carps; fish; zvířata